Timing, origin and emplacement dynamics of mass flows offshore of SE Montserrat in the last 110 ka: Implications for landslide and tsunami hazards, eruption history, and volcanic island evolution. (27th February 2013) - Trofimovs, J.; Talling, P. J.; Fisher, J. K.; Sparks, R. S. J.; Watt, S. F. L.; Hart, M. B.; Smart, C. W.; Le Friant, A.; Cassidy, M.; Moreton, S. G.; Leng, M. J.
Abstract: [1] Mass flows on volcanic islands generated by volcanic lava dome collapse and by larger‐volume flank collapse can be highly dangerous locally and may generate tsunamis that threaten a wider area. It is therefore important to understand their frequency, emplacement dynamics, and relationship to volcanic eruption cycles. The best record of mass flow on volcanic islands may be found offshore, where most material is deposited and where intervening hemipelagic sediment aids dating. Here we analyze what is arguably the most comprehensive sediment core data set collected offshore from a volcanic island. The cores are located southeast of Montserrat, on which the Soufriere Hills volcano has been erupting since 1995. The cores provide a record of mass flow events during the last 110 thousand years. Older mass flow deposits differ significantly from those generated by the repeated lava dome collapses observed since 1995. The oldest mass flow deposit originated through collapse of the basaltic South Soufriere Hills at 103–110 ka, some 20–30 ka after eruptions formed this volcanic center. A ~1.8 km 3 blocky debris avalanche deposit that extends from a chute in the island shelf records a particularly deep‐seated failure. It likely formed from a collapse of almost equal amounts of volcanic edifice and coeval carbonate shelf, emplacing a mixed bioclastic‐andesitic turbidite in a complex series of stages. This study illustrates how volcanic island growth and collapse involved extensive, large‐volume submarine mass flows with highly variable composition. Runout turbidites indicate that mass flows are emplaced either in multiple stages or as single events. Key Points: New multi‐disciplinary offshore stratigraphy reconstruction Identifies temporal variation in eruption style and preservation A culmination of multi‐disciplinary approaches used to refine volcano history